Association study of WNK1 genetic variants and essential hypertension risk in the Northern Han Chinese in Beijing - Liu, Kuo; Liu, Jielin; Liu, Ya; Wang, Hao; Wang, Zuoguang; Liu, Jinghua; Wen, Shaojun (Frontiers in Genetics, 2023)
Background: Essential hypertension (EH) is a complex disorder resulting from interaction of genetic and environmental factors. Lysine deficient protein kinase 1 (WNK1) plays a very important role in maintaining renal potassium, sodium and chlorine ions balance as well as the regulation of blood pressure, so the WNK1 gene is considered a key gene for EH. This study thus sought to evaluate possible genetic associations between the WNK1 genetic variants and EH risk in the Northern Han Chinese population in Beijing. Methods: This study included 476 hypertensive subjects and 491 normotensive subjects. A total of 12 tag SNVs of WNK1 gene were genotyped successfully by TaqMan assay. Comparisons of the genotypic and allelic frequency between cases and controls were made by using the chi-square test. Logistic regression analyses were performed under different genetic models, and haplotype analysis was also conducted. Results: A total of 12 SNVs were identified as the tag SNVs for WNK1 gene. Significant associations were observed between WNK1 gene rs7305099 variant and EH risk, and T allele influenced hypertension risk in a protective manner. After correcting for multiple testing using Bonferroni, the significance remained for the SNV of rs7305099 in three genetic models (allele comparison, P<0.0002, OR=0.627, 95%CI[0.491-0.801]; homozygote comparison, P<0.0003, OR=0.278, 95%CI[0.140-0.552]; additive model, P<0.0003, OR=0.279, 95%CI[0.140-0.553]). In the haplotype analyses, we found that the haplotype A-A-A-C-G-G-G was significantly associated with increased risk for EH (P=0.043, OR=1.23). Conclusions: Our data suggested that the rs7305099 genetic variant and the haplotype A-A-A-C-G-G-G on WNK1 gene might be associated with the susceptibility of EH in the Northern Han Chinese population. These could provide evidences to the risk assessment, early prevention and individualized therapy of EH to some extent.